The employment effects of investment projects - Ole J. Rummel; Thomas Schröder (EIB Papers, 1998)
With some 19 million people out of work, unemployment has become one of the biggest problems facing the EU today. Over the last decade, job creation has been unable to keep up with the increasing size of the active population, leading to a trend of rising unemployment rates for many EU member states. The causes of unemployment in Europe are complex and manifold, but proposals for tackling the problem have so far mainly focused on the supply-side with the aim of making labour markets more flexible. However, the problem may also lie with the demand for labour. Taking into account the fact that investment rates in the EU have declined over the last decade, a focused attempt to stimulate labour demand through investment should also be considered. The relationship between investment and employment creation raises two key questions. First, how much does investment - in the form of an additional ECU one billion, say - actually increase the demand for labour? Second, is it possible to define the kind of investment required to obtain the maximum effect?
Keywords: 330; Investition; Beschäftigungseffekt; Vintage-Modell; Regression; EU-Staaten